THE ROLE OF BUSINESSWOMEN IN IMPROVING FAMILY ECONOMIC WELFARE IN TANETE VILLAGE, SIMBANG DISTRICT, MAROS REGENCY - Nasiruddin, Fadly; Tahir, Thamrin; Najamuddin, Najamuddin (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The role of female traders in improving the economic welfare of families in Tanete Village, Simbang District, Maros Regency is the title of the research conducted by the researcher. This study focuses on determining the role and factors that encourage women to work as traders in improving the economic welfare of families and households in Tanete Village, Simbang District, Maros Regency. This study uses a qualitative research method, namely by conducting observations at the research location, conducting in-depth interviews with 6 (six) informants and also documenting activities in the field. The results of the study obtained by the author are 1) Women who carry out activities or careers as traders can improve the economic welfare of their families or households. Female traders carry out their duties not only in the domestic sector but also in the public sector. Women with the profession of traders can help their families or households from poverty, this is because of the skills they have in trying in this case trading. 2) There are 4 (four) factors for women to enter the business world, namely independence, capital, family and finally coercion.